Strategi Komunikasi Digital @swargaloka.sby dalam Mendorong Partisipasi Perekaman e-KTP Generasi Z di Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya - Diva Mustika Winarto; Fitrotun Niswah; Meirinawati Meirinawati; Eva Hany Fanida (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
The rapid advancement of digital technology demands a transformation in public communication to effectively engage Generation Z as digital natives. Through the Instagram account @swargaloka.sby, the Surabaya City Population and Civil Registration Department aims to drive e-KTP (electronic ID card) registration. Using a descriptive qualitative approach, this study examines digital communication strategies based on the framework of Chaniago and Majid (2024), which encompasses five key aspects: creativity, visual quality, audience alignment, posting consistency, and responsiveness. The analysis reveals that while appealing visuals and communicative language have successfully built audience engagement, actual participation in e-KTP registration remains suboptimal. This is attributed to a relevance gap between population administration issues and the daily lives of young people. The effectiveness of digital communication in driving tangible action depends on the account managers' ability to deliver more persuasive and personally relevant messaging to ensure a sustainable increase in administrative awareness in the digital era.